The Changing Shape of Scotland’s Digital Divide - Wilson Ruth; Hopkins Jonathan (European Countryside, 2019)
The challenges of reaching rural areas with the latest digital technologies are well documented, resulting in a longstanding urban–rural digital divide in many countries. In 2016, Scotland embarked on one of the most ambitious infrastructure projects in Europe when it committed to bringing superfast broadband to all of its citizens by 2021. In this paper, we take stock of recent progress towards this goal by applying the framework of the “Sparsely Populated Area”. While previous work has highlighted that Scotland’s digital divide is shrinking, application of this new framework reveals inequalities that traditional urban–rural classifications mask. We show that, while the number of digital “not spots” has fallen in recent years, many of those remaining are concentrated in a region that faces particular vulnerabilities in terms of service delivery and population decline. Digital inequalities introduce a further challenge to this region in addressing its potential as a viable and attractive place to live and work.